Multicultural Values Represented in English Textbooks for Indonesian Learners: A Social Semiotic Analysis - Aulia Rahmatika Nur Azizah; Erna Andriyanti (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The social semiotic analysis in this study aims to (1) reveal what multicultural values are found in ELT textbooks for ninth-grade learners, (2) explain how the texts and the images in the analyzed textbooks present multicultural values, and (3) uncover how social semiotics dimensions can decode multicultural values. This study finds that among four multicultural values discovered in the textbooks, responsibility to the world community has the most frequent appearance while respect for human dignity and universal human rights has the least frequent appearance. Those values are presented denotatively and connotatively through texts, images, and texts-images. Based on the findings, textbook authors are recommended to include more content and add learning activities that facilitate discussions and reflections on multiculturalism. In addition, this research suggests that English teachers who use these textbooks add learning activities that enable students to discuss multicultural values since, in this study, multicultural values are mainly presented connotatively.